Ethical Commitment of Universities in the Face of the Need to Strengthen Scientific Research for Development - Gómez Sánchez Soto, Rubén; Rojas Cangahuala, Gladys Madeleine; Días Ochoa, José Eduardo (LACCEI, 2024)
Abstract– The universities should have a high degree of impact on the development of countries, for which it is necessary for them to establish their own prospective plans or future building plans. According to the results shown in the present research, two key conditions have been identified to improve certainty about the right path. The first condition is the strengthening of ethics, which according to the Royal Academy of Spain defines ethics as a set of moral norms that govern human behavior in any area of life and are necessary to guarantee collective well-being. This concept has been taken as a key factor in the training and guidance, profile, competencies, and capabilities of the professionals that universities provide to the countries. The other condition is the main objective of the present work, which is to design a conceptual model on the ethical commitment of universities in the face of the need to strengthen scientific research for development. This model is supported through the synergy between two variables, the first: universities that should gradually ascend from the first to the second mission, and then to the third mission and economic impact. And the other is the application of the definition of ethics in its full scope and importance, as part of scientific competencies, as a guide for researchers, applied to science and research. Therefore, the results of the research on the failures in the scientific integrity of Latin American research personnel are of great concern.